Espaço público e “nova urbanidade” no contexto do direito á cidade - Ana Fani Alessandri Carlos (Confins)
The challengeof thinkingthe city in itsspatial perspectiveoffersknowledge thatinvolves the constructionofa theory ofsocio-spatial urban practice, in ordertoreveal thesense of realityas a whole andtheopportunitiesthat are emerginginthehorizonfor everyday lifein the city.It is inthisperspective that is placeda criticalreflection on the meaningof sociallong-term reproductionof urban space-capable of illuminatingthe trapof reducing thesense of the cityon the conditionofreproductionforceor capital, meaninglessspaceof life orcitizenship andindividual experience.Sothe public space asspace-timein the cityreveals thateach subjectis located ina specificspace, builtby a network ofexperiencedmeaningsin termsofexperienceas a socio-spatial practice.Thusspace has a) a real and concreteobjectivity, and b) asubjectivedimension: therealization thatcitizensbuild ofreality.Theseare not independentand allowintheir dialectical play an understandingof thepractical and abstractdimensionsof spatialproduction.Thus, the cityas a product ofhuman action isthe objectificationwhich gives itits historical and socialcontent,isat the same time, the subject becomesaware of thisproduction.